PRELIMINARY OBSERVATION ON THE USE OF UNDER -WATER LIGHT IN FISH CATCH - BISWAS, K P; MOHANTY, S K (Fishery Technology, 2025)
Experiments with drift gill net] with under-water lights werecarried out in the sea and estuarine region along with a control net ofthe same specifications without any light in the same fishing groundfor comparison. The experimental net caught more fish in numberand weight than the control. Fishes like pomfrets (Pampus chinensis,Parasfromafeus niger), seer (Scomberomorus spp), hilsa (lfisha spp)etc showed positive phototaxis and were giBed encircling the point ofiHumination. Young skates (Mobu!a spp) and Po!ynemus tetradacty!us were antiphototactic. The number of fishes caught increasedwith increase in period of iHumination. The catch of larger fisheswas maximum at 60 mts of i11umination and the total catch increasedwith increase in intensity of light. Additional cost of operation withunder-water light was Rs 1-25 per hr but the catch was 4 to 5 timesgreater than that of the control net.